An exploratory numerical study of a diesel/methanol dual-fuel injector: Effects of nozzle number, nozzle diameter and spray spacial angle on a diesel/methanol dual-fuel direct injection engine. (15th June 2022) - Li, Zhiyong; Wang, Yang; Yin, Zibin; Gao, Zhanbin; Wang, Yongjian; Zhen, Xudong
Highlights: Parameters of a diesel/methanol dual-fuel injector are investigated. More nozzles are good for fuel economy but not for ringing intensity. More nozzles contribute to the reduction of soot, THC, CO, and CH2 O emissions. 8 nozzles and a β of 10° are the most appropriate injector parameters. Abstract: Methanol direct-injection makes it possible to the application of methanol at a high substitution ratio in diesel engines, but it is difficult to add a methanol injector to the already compact cylinder head. Therefore, an idea of a diesel/methanol dual-fuel injector is proposed, which can overcome both the inconvenience of arranging two injectors on the cylinder head and the disadvantage that the two injectors cannot be located in the center of the piston pit simultaneously. A three-dimensional simulation model coupled with chemical reaction kinetics is used to explore the effect of dual-fuel injector parameters including nozzle number and diesel/methanol spray spatial angle ( β ) on a diesel/methanol dual-fuel direct injection engine. The results show that more nozzles and smaller nozzle diameter contribute to fuel economy as well as the reduction of soot, THC, CO, and CH2 O emissions, but higher ringing intensity (RI) and NOx emissions. It is found that 8 nozzles are the most suitable after weighing fuel economy, RI, and emissions. Secondly, influenced by the in-cylinder airflow, there exists an optimal spray spatial angle ( β = 10°) to obtain the best fuel economy and emissions.